2019
DOI: 10.1155/2019/1952538
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life before and after Sleeve Gastrectomy in Lebanese Population

Abstract: Introduction. Obesity is increasing worldwide and in Lebanon with a negative impact on the quality of life. The primary objective of this study is to measure the quality of life in obese subjects before and after bariatric surgery, depending on age, sex, and degree of weight loss. A secondary objective is to determine the impact of bariatric surgery on comorbidities associated with obesity. Materials and methods. Patients undergoing laparoscopic sleeve gastrectomy for BMI ≥ 30 kg/m2 between August 2016 and Apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
6
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
6
6
0
4
Order By: Relevance
“…Regarding the obesity-related comorbidity, the current study showed that nearly half of the study and control groups were suffering from hypertension and nearly one-quarter of them were suffering from DM (type I & II), while there was no statistically significant difference between the two groups. These results were consistent with Alkassis et al, (23) who conducted a study to assess the QOL pre and post weight loss surgery among the Lebanese population, and reported that a large proportion of the participants were hypertensive, diabetic and dyslipidemic.…”
Section: -Implementation Phasesupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding the obesity-related comorbidity, the current study showed that nearly half of the study and control groups were suffering from hypertension and nearly one-quarter of them were suffering from DM (type I & II), while there was no statistically significant difference between the two groups. These results were consistent with Alkassis et al, (23) who conducted a study to assess the QOL pre and post weight loss surgery among the Lebanese population, and reported that a large proportion of the participants were hypertensive, diabetic and dyslipidemic.…”
Section: -Implementation Phasesupporting
confidence: 91%
“…Bahgat, (28) who mentioned that improving the level of knowledge in patients had a significant impact on reducing or preventing postoperative complications, improving the quality of life, and improve health. These findings were supported by another study held by Alkassis et al, (23) who reported that the weight loss surgery improves QOL and allows the reduction of concomitant diseases.…”
Section: -Implementation Phasesupporting
confidence: 72%
“…A caracterização dos resultados está descrita no Quadro 1. Dos artigos, notou-se que a técnica cirúrgica de Sleeve e Bypass gástrico, foram os procedimentos mais frequentes (Lechaux, Foll & Rascle, 2020;Akkayaoglu & Çelik, 2020;Cherick et al, 2019;Castanha et al, 2018;Major et al, 2016;Alkassis et al, 2019;Griauzde et al, 2018;Mendes &Vargas, 2017;Vegel et al, 2017;Tarride et al, 2016). Somente um Research, Society and Development, v. 10, n. 3, e31410313329, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i3.13329 estudo (Edward et al, 2018) foi realizado exclusivamente com participantes do sexo masculino.…”
Section: Resultsunclassified
“…Ao diminuir o peso corporal, houve melhora no perfil bioquímico (Oliveira et al, 2018;Castanha et al, 2018;Alkassis et al, 2019;Mendes & Vargas, 2017). Observou-se também, que a cirurgia bariátrica foi eficaz para minimizar os efeitos e/ou sintomas das comorbidades, como diabetes mellitus e hipertensão arterial (Lechaux, Foll & Rascle, 2020;Yilmaz & Yilmaz, 2019;Castanha et al, 2018;Vegel et al, 2017;Alkassis et al, 2019;Mendes & Vargas, 2017).…”
Section: Classe I Transformações Físicas Após a Cirurgia Bariátricaunclassified
See 1 more Smart Citation